Water Monitor Lizard (Varanus salvator) Skin Microstructure: Histochemical and Morphometrical Studies of Fiber Type Characteristics (Histochemistry Fiber Skin Water Monitor) - Prawira, Andhika Yudha; Phadmacanty, Ni Luh Putu Rischa; Semiadi, Gono; Kurniati, Hellen; Trilaksono, Wahyu; Yulianto; Nurhidayat; Agungpriyono, Srihadi (HAYATI Journal of Biosciences, 2024)
Global demand for the water monitor’s skin, Varanus salvator, has made it a valuable wildlife commodity. Leathercraft manufacturing must consider not only beauty but also the strength and flexibility of the leather, which is determined by its structure in the skin. Therefore, this study analyzed and evaluated the fiber type characteristic of the water monitor’s skin. Skin samples were collected from 10 Sumatra water monitors with a Snout-Vent Length size of 39-89 cm and were divided into small (39-59 cm) and large (60-89 cm) groups. The skins from the dorsocervical, lumbosacral, and ventral regions were proceeded for histological sections. Histochemical approaches utilized were Hematoxylin Eosin, Picrosirius Red, and Elastin Verhoeff’s Hematoxylin staining methods. Thick fibers are the main component in the skin, ranging from 69-73%, respectively, while thin fibers varied greatly and were observed predominantly in the reticular dermis. Fiber size in the reticular dermis of small lizards was lower than that of larger ones. Elastic fibers were observed abundantly at the border of the reticular dermis and subcutaneous layer in both small and large lizards. Moreover, the skin of the small-sized lizard also has a lower morphometric than that of a large-sized lizard, both in thickness and fiber type percentage. Therefore, the skin of small-sized lizards was considered less tough than that of large-sized lizards.